Inferring population dynamic trends of Nothofagus pumilio and N. betuloides in coastal and mountain forests of Tierra del Fuego: contrasting from flowering to seedling survival through several reproductive cycles - Toro Manríquez, Mónica del Rosario (2021)
Transition from fower to seedling encompasses major processes that defne the success of the tree regeneration, and consequently, its study is crucial in the context of forest management. Here, we analysed the transition probability of the reproductive cycle of two Nothofagus species, which formed pure and mixed forests in coastal and mountain geographic locations of Tierra del Fuego (Argentina). Pure deciduous N. pumilio (Np), pure evergreen N. betuloides (Nb), and mixed N. pumilio–N. betuloides (M) forests in coasts and mountains (3 forest types×2 geographic locations×20 replicas=120 replicas) were evaluated. Reproductive structures (female fowers, fruits, seeds, sound seeds, emerged seedlings and surviving seedlings up to 2 years) were studied since 2012–2018. Our results suggested that transition probabilities from fower to surviving seedlings varied inter-annually between N. pumilio and N. betuloides. The hazard ratio in the transition showed an infuence of the cohorts and the geographic location on N. pumilio, while forest type and geographic location infuenced on N. betuloides. Flower to fruits and seed to seedling were the most critical process in all forest types and locations. Cumulative transition probabilities (female fowers to 2-year-old seedlings) for N. pumilio were 0.3–46.2% in Np and 1.4–30.2% in M, and pure and mixed forests reached similar probabilities only in cohort 3. For N. betuloides, these were 2.8–24.4% in Nb and 0.0–6.5% in M. Both Nothofagus species showed a better performance of pure forests in mountains (15.9–46.2% Np; 3.8–24.8% Nb) than in coasts (0.3–16.1% Np; 2.8–5.3% Nb). Through this integrated approach, considering the full reproductive cycle, it is possible to quantify the infuence of canopy composition and inter-annual variability in natural forest dynamic, and allows to identify the critical stages of tree recruitment in pure and mixed Nothofagus forests.